The Influence of Placement and Competency on Motivation and Its Implications for the Performance of Bhayangkara Hospital Jambi Employees - Rahma Agustina; M. Zahari; Osrita Hapsara (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to find out and analyzeThe influence of placement and competency on motivation and its implications for the performance of Bhayangkara Hospital Jambi employees. This type of research uses descriptive and verification research. The object of this research is the 93 employees of Bhayangkara Hospital Jambi. This research uses the path analysis method (Path Analysis). Based on the results of the questionnaire regarding the placement of the score, it is 10,872 which is included in the "Very Suitable" category. Then the description of the competency variable shows that it is included in the "Very High" category with a total score of 17,297. Then to describe the motivation variable, it shows that the score obtained was 7,419 which is included in the "High" category. Meanwhile, the description of employee performance variables shows that the score obtained was 10,857 in the "Very High" category. Based on the research results, placement and competency directly and indirectly influence motivation, placement and competency directly and indirectly influence employee performance, motivation influences employee performance. Then placement and competency through motivation have an influence on the performance of Bhayangkara Jambi hospital employees.